MEDIAN LINE IMMETRITY AT CENTRIC OCCLUSSION IN FKG UNMAS DENPASAR : KARAKTERISTIK KESIMETRISAN GARIS MEDIAN GIGI DENGAN GARIS MEDIAN WAJAH SAAT OKLUSI SENTRIS PADA MAHASISWA FKG UNMAS DENPASAR - Norman Hidajah; Ketut Virtika Ayu (Interdental Jurnal Kedokteran Gigi (IJKG), 2021)
Introduction: Facial appearances especially teeth and face are some of the most important things in this era. The symmetry of the dental median line with the facial median line needs to be considered to create a balanced, harmonious, and attractive facial structure, especially when smiling. The position of the maxillary median line to the facial median line is an important factor in orthodontic diagnosis. This research aims to obtain the symmetry of the dental median line with the facial median line during centric occlusion in dentistry students of Mahasaraswati University of Denpasar. Materials and Methods: The type of this research is descriptive with a cross-sectional approach that involved 57 participants. Results and Discussions: The results of this research are the percentage of the students whose dental median line with a facial median line is symmetrical (≤1 mm) was 77% that obtained 44 participants, while the percentage of students who had a dental median line with a facial median line is not symmetrical (> 1 mm) were 23 % that obtained 13 participants with a shift of median line 2 mm in 7 participants, 3 mm in 5 participants, and 5 mm in 1 participant. Conclusion: Based on the results it can be concluded that thedentistry students of Mahasaraswati University of Denpasar whose dental median line with their facial median line was symmetrical is more dominant than those who were not symmetrical.